2019
DOI: 10.1177/1099636219839161
|View full text |Cite
|
Sign up to set email alerts
|

Analytical solution for magneto-thermo-elastic responses of an annular functionally graded sandwich disk by considering internal heat generation and convective boundary condition

Abstract: In this paper, an exact solution for stress distribution of a rotating sandwich disk subjected to magnetic, thermal fields, and convection heat transfer with the consideration of internal heat generation is presented. The sandwich disk is composed of three different layers in which the central layer is made of functionally graded material, whereas the inner and outer layers are made from pure metal and ceramic materials, respectively. All mechanical and thermal properties of the central layer are assumed to ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…In this section, some numerical results are obtained and represented in Figs. 4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22 and 23 in order to illustrate the current solution of the FGP micro-rotating cylinder problem, where the effects of flexoelectricity, non-homogeneity constant, magnetic field, angular velocity and characteristic length parameter on the radial and circumferential stresses, radial displacement and electric potential distributions along the cylinder thickness are graphically shown. The mechanical and electric properties of lead zirconate titanate (PZT-4) for the FGP micro-rotating cylinder are listed in Table 1 [ are adopted based on [55,85,86].…”
Section: Fgp Micro-rotating Cylinder Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…In this section, some numerical results are obtained and represented in Figs. 4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22 and 23 in order to illustrate the current solution of the FGP micro-rotating cylinder problem, where the effects of flexoelectricity, non-homogeneity constant, magnetic field, angular velocity and characteristic length parameter on the radial and circumferential stresses, radial displacement and electric potential distributions along the cylinder thickness are graphically shown. The mechanical and electric properties of lead zirconate titanate (PZT-4) for the FGP micro-rotating cylinder are listed in Table 1 [ are adopted based on [55,85,86].…”
Section: Fgp Micro-rotating Cylinder Problemmentioning
confidence: 99%
“…Due to distinct properties of functionally graded piezoelectric (FGP) materials, such materials have always been appealing to researchers. In recent years, many researchers have investigated the behavior of FGP cylinders, spheres and plates under diverse multi-physical loading [12][13][14][15][16]. Akbarzadeh and Pasini [17] used a multi-physics model to study the effect of moisture, temperature, magnetic, electric and mechanical loadings on the response of multilayered and functionally graded cylinders.…”
Section: Introductionmentioning
confidence: 99%
“…In order to reduce the magnitude of tangential stresses in thick-walled functionally graded cylinder, researchers have considered a sandwich composition of functionally graded material at an inner layer and composite material at an outer layer of the cylinder. The investigation revealed that material composition of a sandwich cylinder has significant influence on the behavior of radial and tangential stress under thermo-mechanical, magneto-thermo-mechanical loading conditions, internal heat generation and convective boundary conditions [ 20 , 21 , 22 ]. [PDM]With the advent of functionally graded materials, research work on steady state creep stresses and strains has gained impetus due to its ability to provide reduced stress concentration and smooth variation of reinforcement material volume from one surface to other surface of the body.…”
Section: Introductionmentioning
confidence: 99%
“…Along the same lines, many researchers investigated the behaviors of a sandwich disc in a magnetic field environment. Dini et al [24] presented an exact solution for the behaviors of a rotating sandwich disc subjected to both magnetic and thermal fields. The magnetothermoelastic response of a sandwich disc, subjected to nonuniform thermal load, was investigated by Zenkour [25].…”
Section: Introductionmentioning
confidence: 99%